46-52 MENINGKATKAN EKONOMI, SUMBER DAYA MANUSIA, DAN POTENSI DI DESA JELEGONG DENGAN MEMODERNISASI BISNIS MIKRO SETEMPAT - afandi, guntur nur; kusuma, indrawan; yudiantini, sintia; purnama, yosef (Fakultas Teknik Universitas Islam Nusantara, 2020)
Jelegong Village is one of the areas in the Rancaekek sub-district, Bandung Regency, where the average population is farming, labor and entrepreneurship. However, the technology used is still traditional, such as marketing of finished products which only sell to other traders, not online through the marketplace so that the target market can be wider. Seeing the condition of Jelegong Village, there is still a lot to be developed, we decided to carry out PkM activities in the village. The formulation of the problem, among others, is that the economy of Jelegong Village is declining due to the Covid-19 Pandemic. The results obtained from solving the problems of partners or the target community of the program using the applied method. With soap training, people know how to make liquid soap, know the ingredients that can be used to make soap, and are expected to be able to make their own soap at home. So that it can save costs for purchasing soap because if you make it yourself you can produce a lot of liquid soap at an economical price, or even if the community wants to be an entrepreneur, the community can produce and market the liquid soap product.Keywords: Economy, HR, Village potential